Integrins Modulate T Cell Receptor Signaling by Constraining Actin Flow at the Immunological Synapse - Jankowska, Katarzyna I.; Williamson, Edward K.; Roy, Nathan H.; Blumenthal, Daniel; Chandra, Vidhi; Baumgart, Tobias; Burkhardt, Janis K. (Frontiers in Immunology, 2018)
Full T cell activation requires coordination of signals from multiple receptor-ligand pairs that interact in parallel at a specialized cell-cell contact site termed the immunological synapse. Signaling at the immunological synapse is intimately associated with actin dynamics; TCR engagement induces centripetal flow of T cell actin network, which in turn enhances the function of ligand-bound integrins by promoting conformational change. Here, we have investigated the effects of integrin engagement on actin flow, and on associated signaling events downstream of the TCR. We show that integrin engagement significantly decelerates centripetal flow of the actin network. In primary CD4+ T cells, engagement of either LFA-1 or VLA-4 by their respective ligands ICAM-1 and VCAM-1 slows actin flow. Slowing of actin flow is greatest when T cells interact with low mobility integrin ligands, supporting a predominately drag-based mechanism. Using integrin ligands presented on patterned surfaces, we demonstrate that the effects of localized integrin engagement are distributed across the actin network, and that focal adhesion proteins such as talin, vinculin, and paxillin are recruited to sites of integrin engagement. Further analysis shows that talin and vinculin are interdependent upon one another for recruitment, and that ongoing actin flow is required. Suppression of vinculin or talin partially relieves integrin-dependent slowing of actin flow, indicating that these proteins serve as molecular clutches that couple engaged integrins to the dynamic actin network. Finally, we found that integrin-dependent slowing of actin flow is associated with reduction in tyrosine phosphorylation downstream of the TCR, and that this modulation of TCR signaling depends on expression of talin and vinculin. More generally, we found that integrin-dependent effects on actin retrograde flow were strongly correlated with effects on TCR signaling. Taken together, these studies support a model in which ligand-bound integrins engage the actin cytoskeletal network via talin and vinculin, and tune TCR signaling events by modulating actin dynamics at the immunological synapse.